46. Normal intraepidermal nerve fiber density at lower limb. Issue 12 (December 2016) - Provitera, V.; Donadio, V.; Caporaso, G.; Stancanelli, A.; Liguori, R.; Santoro, L.; Nolano, M.
Abstract : Intraepidermal nerve fiber (IENF) density at distal leg is considered sufficient to confirm the clinical suspect of small fiber neuropathy. Extensive normative datasets demonstrate a reduced nerve density with ageing and in male compared to female subjects at this site. An additional sample from thigh is often analyzed to calculate leg/thigh IENF density ratio and assess the length dependence of the neuropathy. Nonetheless, only small populations have been published reporting thigh IENF density. We applied standard techniques to assess IENF density from thigh and leg of 207 healthy subjects, (M/F = 88/119), age 49.1 ± 14.2 years (range 18–82) and to calculate leg/thigh density ratio. IENF density was 14.3 ± 3.5 at the leg and 22.5 ± 4.2 at the thigh. IENF density decreased with age at both sites. Female subjects showed a higher density of IENF compared to male subjects at the distal site only. Average leg/thigh density ratio was 0.64 ± 0.13. This value decreased with age and differed between female (0.66 ± 0.13) and male (0.62 ± 0.13) subjects. Lower limb IENF analysis shows that age affects nerve density in both proximal and distal sites. Leg/thigh ratio is slightly higher in female compared to male subjects. The gender related IENF density differences observed distally are not evident at the proximal site.